Pain Detect as A Tool for The Screening of Neuropathic Pain in Patients with Diabetes Mellitus - Agnes Annurul Maulidia; Media Yuni Kurniawati; Andreas Adiwinata Then (Magna Neurologica, 2024)
Background: Diabetic neuropathy (DN) is a prevalent long-term complication of diabetes mellitus (DM), affecting more than 50% of patients. In addition, several studies also showed that distal symmetric polyneuropathy (DSPN) accounts for 75% of all DN cases. To facilitate the treatment of DN, painDETECT questionnaire, a self-reported tool with 85% sensitivity and 80% specificity, has been recommended for detecting neuropathic component in pain. Objective: This study aimed to promptly diagnose DN using painDETECT questionnaire in DM patients. Methods: The study procedures were carried out using a descriptive, cross-sectional design with 67 DM patients from Cibabat Regional Hospital Department of Internal Medicine outpatient clinic through consecutive sampling in October–November 2022. Primary data were obtained using the adapted and validated Indonesian painDETECT questionnaire. Results: Among the 67 patients, 32.9% experienced neuropathic pain with a score of 19–38, indicating the involvement of >90% of neuropathic pain components. Sensory deficits, such as numbness, burning sensation, pins-and-needles, and allodynia, were observed in 86.3%, 90.1%, and 72.7% of patients with neuropathic pain, respectively. In addition, a total of 59.7% of participants (n=40) reported the presence of mild pain (NRS 3). Conclusion: Based on the results, the majority of patients had complaints of neuropathic or mild pain (40 subjects; 59.7%). Among the 22 patients experiencing neuropathic pain, 54.5% reported mild intensity.